Antenatal perspective of hypoplastic left heart syndrome: 5 years on. Issue 3 (29th June 2007) - Rasiah, S V; Ewer, A K; Miller, P; Wright, J G; Barron, D J; Brawn, W J; Kilby, M D
Abstract : Background: Palliative staged reconstructive surgery has radically altered the outcome of babies with hypoplastic left heart syndrome (HLHS). Aim: To compare the current outcome of antenatally diagnosed HLHS with a series 5 years previously now that paediatric cardiothoracic and postnatal paediatric intensive care techniques have been further refined. Method: Comparison of all cases of HLHS diagnosed antenatally at Birmingham Women's Hospital between 1 January 2000 and 31 December 2004 with results of the previous series. Results: 79 fetuses were identified with HLHS. The median gestational age at diagnosis was 22 weeks. After counselling, 20 (25.3%) couples terminated the pregnancy compared with 43.7% in the previous cohort (p = 0.01). Of the 59 couples who continued with the pregnancy, four had stillbirths and two were lost to follow-up. Subsequently, there were 53 live births, of which six babies had an alternative major congenital heart disease diagnosed postnatally; 10 babies were not considered for surgery (parents' wishes) and died after compassionate care; 31 babies underwent surgery. The early (30 days) surgical mortality after stage 1 Norwood procedure was 19.4% and 20 patients are still alive. In the cohort of intention-to-treat cases, the overall survival was 46.9% (23/49). Conclusion: The number of parents choosing termination after an antenatal diagnosis of HLHS has almost halved since 5 years ago. Despite the significant increase in surgical survival following stage 1 Norwood in this period, in the intention-to-treat cohort the survival was 46.9%. These data again highlight the poorer outcome for babies with congenital malformations diagnosed in utero in comparison with those identified postnatally.